Diversity and prevalence of parasitic infestation with zoonotic potential in dromedary camel (Camelus dromedarius) and fat-tailed sheep (dhumba) in Bangladesh - Islam, Ariful; Islam, Shariful; Ferdous, Jinnat; Rahman, Md Kaisar; Uddin, Md Helal; Akter, Sazeda; Rahman, Md Hafizar; Hassan, Mohammad Mahmudul (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: Parasitic infestation is a major cause of losses in livestock production in tropical regions. A cross-sectional study was conducted to determine the prevalence of Gastro-intestinal (GI) parasites of dromedary camel (Camelus dromedarius) and fat-tailed sheep (dhumba), and the prevalence of hemoparasites in camel from Dhaka, Bangladesh. Materials and Methods: A total of 87 fecal samples (32 dhumba and 55 camel) and 55 camel blood samples were collected during September–October 2015. Fecal samples were examined by direct smear, sedimentation method, flotation technique, and McMaster technique for GI parasite. Giemsa stained blood smears were examined under microscope for hemoparasite detection. Results: 62% camel (n = 34; 95% confidence interval (CI): 47.7–74.6) were infected with at least one genus of parasite. 15% camel were harboring more than one genus of parasite. The prevalence of GI parasite and hemoparasite in camel were recorded as Trichuris spp. (n = 16; 29%; 95% CI: 17.6–42.9), Balantidium coli (n = 12; 22%; 95% CI: 11.8–35.0), Trichostrongylus spp. (n = 7; 13%; 95% CI: 5.3–24.5), Strongyloides spp. (n = 5; 9%; 95% CI: 3.0–20.0), Anaplasma spp. (n = 5; 9%; 95% CI: 3.02–20.0), Paragonimus spp. (n = 1; 2%; 95% CI: 0.05– 9.7), Schistosoma spp. (n = 1; 2%; 95% CI: 0.05–9.7), Hymenolepis spp. (n = 1; 2%; 95% CI: 0.05–9.7), Moniezia spp. (n = 1; 2%; 95% CI: 0.05–9.7), and Babesia spp. (n = 1; 2%; 95% CI: 0.05–9.7). Mean EPG feces of camel was 291.76 ± 42.03 with a range of 0–1,400. Total 59.4% dhumba (n = 19; 95% CI: 41–76) were positive for GI parasite, including Trichostrongylus spp. (n = 10; 31.3%; 95% CI: 16.1–50), Strongyloides spp. (n = 9; 28%; 95% CI: 13.8–46.8), B. coli (n = 5; 15.6%; 95% CI: 5.3–32.8), and Trichuris spp. (n = 4; 12.5%; 95% CI: 3.5–28.9). Conclusions: High percentage of parasitic infestation in camel and dhumba in the present study refers to the necessity of use of anthelmintic for health and production improvement and to prevent zoonotic parasite transmission to animal handler and workers. J. Adv. Vet. Anim. Res., 6(1): 142-147, March 2019